Countering Violent Extremism in Pakistan : Local Actions, Local Voices - Weiss Anita M. (Karachi Oxford University Press, 2020)
This book identifies and analyzes the impact of the various ways in which local people are responding, taking stands, recapturing their culture, and saying 'stop' to the violent extremism that has manifested over the past decade (even longer) in Pakistan. Local groups throughout Pakistan are engaging in various kinds of social negotiations and actions to lessen the violence that has plagued the country since the 1979 Soviet invasion of Afghanistan which let loose a barrage of violence that overflowed into its borders. In so many ways, Pakistanis are engaging in powerful actions that transform how people think about their own society, impeding extremists' rants while acting on 'envisioning alternative futures'. This book, hence, focuses on finding the sparks of hope that local people are creating to counter violent extremism based on close ethnographic study of ground realities about not only what people are doing but why they are selecting these kinds of actions, how they are creating alternative narratives about culture and identity, and their vision of a future without violence. This book is also designed to celebrate what is flourishing in cultural performances, music, social activism, and the like in Pakistan today because of people's commitment to take stands against extremism.
Include Color Illustrations, Tables, Bibliography and Index
Keywords: Domestic terrorism